Eosinophilic esophagitis in Japanese patients: A mild and slow-progressing disorder - Sato, Hiroki (PLoS One, 2018)
BACKGROUND AND AIM: Awareness of eosinophilic esophagitis (EoE) has gradually increased in Japan, therefore the characteristics of this disease in the Japanese patient population need to be elucidated. This study aimed to investigate the features of EoE in the Japanese population. METHODS: During a 2-year period, all gastrointestinal endoscopies were performed with maximum attention being paid to identify EoE through endoscopic findings. Clinical features and findings were analyzed among this population. RESULTS: Among a total of 8589 patients (general gastrointestinal endoscopy, performed for evaluation of symptoms or disease follow-up: 3669; medical check-up endoscopy, routinely performed in asymptomatic patients: 4920), 17 patients (0.20%) were diagnosed with esophageal eosinophilia (mean age ± standard deviation: 44±11.9 years; 1 female). Only 6 patients with esophageal eosinophilia were diagnosed by general gastrointestinal endoscopy; among them, 3 patients had dysphagia and 3 were asymptomatic. The remaining 11 patients were diagnosed by medical check-up endoscopy. All patients were treated with a proton pump inhibitor (PPI); 5 were diagnosed with EoE and 12 with PPI responsive esophageal eosinophilia. Chronological endoscopy analysis showed that EoE findings could be observed for a mean of 6.1 years prior to diagnosis, and the disease did not significantly progress in severity. CONCLUSIONS: Most Japanese patients with EoE have mild and slowly progressing disease, which can be diagnosed when close attention is paid to the endoscopic findings. Medical check-up endoscopy in Japan could be a great opportunity for the early diagnosis of EoE.